Cognitive modeling : a linguistic perspective - Ruiz de Mendoza Ibáñez, Francisco José, 1961-; Masegosa, Alicia Galera (Human cognitive processing, 2014)
This monograph studies cognitive operations on cognitive models across levels and domains of meaning construction. It explores in what way the same set of cognitive operations, either in isolation or in combination, account for meaning representation whether obtained on the basis of inferential activity or through constructional composition. As a consequence, it makes explicit links between constructional and figurative meaning. The pervasiveness of cognitive operations is explored across the levels of meaning construction (argument, implicational, illocutionary, and discourse structure) disti.